Rancang Bangun Sistem Informasi Penilaian PKL Rekam Medis (APIKAL) Berbasis Web - Dwi Nugroho; Rizky Yuspita Sari; Untoro Dwi Raharjo; Tika Sari Dewi (STIKOM Tunas Bangsa Pematangsiantar, 2026)
The internship evaluation process at the Diploma 3 Program of Medical Records and Health Information (RMIK), Universitas Jenderal Achmad Yani Yogyakarta, previously relied on open shared spreadsheets. This existing system posed a high risk of data manipulation, such as unauthorized copying and pasting of grades due to weak user access control, and led to delays in grade recapitulation because tracking the progress of clinical instructors at partner hospitals was difficult. This study aims to design and implement the Medical Record Internship Evaluation Information System (APIKAL) as a secure and efficient digital solution. The system was developed using the Prototyping method, utilizing Google Sheets as the database alongside HTML and Google Apps Script to create a Web App-based user interface. The functional quality of the system was evaluated using Black Box Testing. The results indicate that APIKAL successfully eliminates the vulnerability of grade manipulation by strictly enforcing role-based access control for three main actors: the Internship Coordinator, Academic Advisors, and Clinical Instructors. Beyond enhancing data security, the system automatically calculates final grades and maps them into Outcome-Based Education (OBE) Learning Outcomes in real-time. The Black Box Testing confirmed that all features functioned with 100% validity. In conclusion, the APIKAL system is highly feasible for full implementation to support secure, rapid, and accountable internship administration.